Методологія управління змінами в інтегрованих аграрних виробничих системах - Третяк, Антон Валерійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті розглянуто основні аспекти методології управління змінами в інтегрованих аграрних виробничих системах. Аграрний сектор, який зазнає швидких змін під впливом глобалізації, технологічного прогресу та зростаючої конкуренції, потребує впровадження інноваційних підходів до управління для забезпечення стійкого розвитку. Основною проблемою, яка виникає при управлінні змінами, є недостатній рівень технологічної готовності аграрних підприємств та фінансові труднощі, що обмежують інвестиції в інноваційні проєкти. Акцентується увага на необхідності розробки структурованого підходу до управління змінами, який передбачає планування, реалізацію та моніторинг змін з метою підвищення ефективності аграрних підприємств. У статті також підкреслюється важливість гнучкості організаційних структур і адаптації до зовнішніх ринкових умов, таких як кліматичні зміни та нові екологічні вимоги. На основі досліджень Світового банку, Європейської комісії та ФАО, у статті наводяться приклади впливу впровадження інноваційних технологій на продуктивність підприємств.

The article delves into the key aspects of changing management methodology in integrated agricultural production systems. The agricultural sector, amidst rapid transformations influenced by globalization, technological progress, and increasing competition, needs innovative management approaches to ensure sustainable development. While the insufficient level of technological readiness and financial constraints pose challenges, the potential benefits of successful change management, such as increased productivity and sustainability, are promising. Overcoming resistance from staff and establishing well-defined mechanisms for managing change will be crucial in this journey. In this context, the authors stress the pivotal role of leadership in management change. A structured approach, involving careful planning, implementation, and monitoring, is essential to enhance the efficiency of agricultural enterprises. With active support from leadership, successful management changes become feasible. The application of innovative technologies, capable of boosting productivity while reducing costs, further empowers the leadership in driving change. The article also underscores the importance of flexibility in organizational structures and the ability to adapt to external market conditions, including climate change and evolving environmental requirements. Drawing on research from the World Bank, the European Commission, and the Food and Agriculture Organization (FAO), the article provides examples of how adopting innovative technologies has positively impacted the productivity of agricultural enterprises. Modern information technologies, such as precision agriculture and automated control systems, are noted for their role in optimizing management processes.
Methodology of change management in integrated agricultural production systems
Keywords: управління змінами; аграрні підприємства; інтеграція; виробничі системи; інновації; технологічна готовність; фінансові інвестиції; конкурентоспроможність; трансформація; change management; agricultural enterprises; integration; production systems; innovations; technological readiness; financial investments; competitiveness; transformation